ANALYSIS OF PNEUMONIAASSOCIATED MORTALITY OF MONKEYS IN CAPTIVITY AND THE ROLE OF METHICILLIN-SENSITIVE STAPHYLOCOCCUS AUREUS (MRSA) IN THE RECOVERED MICROFLORA SPECTRUM - V. A. Kalashnikova; A. V. Demerchyan (Ветеринария сегодня)
Pneumonia-associated mortality of different monkey species in captivity in 2017 has been analyzed. The animal death frequency and seasonality was demonstrated. Pneumonia-associated mortality in baby monkeys and old monkeys exceeds the mortality of infants and mature animals. The maximum pneumonia-mortality rate in monkeys was observed in February, April and May. The spectrum of microorganisms recovered from lungs of dead animals was identified. The prevailing bacterial flora detected in case of pneumonia was Staphylococcus aureus (43.1%) and Escherichia coli (34.9%), which were detected both in monoculture and communities. One of the peculiarities of pneumonia in monkeys is high occurrence of polymicrobial communities. Most frequently S. aureus is observed in combinations with E. coli (52.5%). All recovered S. aureus cultures were methicillin-sensitive and did not have gene mecA in their genome. During performance of bacteriological tests of autopsy material the lung tissue samples can get contaminated with the foreign flora that’s why it’s quite difficult to speak about the role of these and those microorganisms as major disease agents.